Preparation method of silicon / doped silicon porous nanosheet
By using the reaction of sodium silicate and ammonium salt to form a sol in the process of preparing silicon/doped silicon porous nanosheets, the problems of high preparation costs and difficult to regulate in the prior art are solved through steps such as magnesium heat treatment and acid washing, and the problems of high production costs and difficult to regulate performance in the prior art are realized, and the electrochemical performance and cyclic stability of the material are significantly improved.
Patent Information
- Application Number
- CN202411849745.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art has problems such as high production costs, cumbersome processes, and difficult to regulate the microstructure and lithium storage performance when preparing two-dimensional porous silicon nanosheets. At the same time, it is difficult to achieve uniform distribution of doped elements in silicon materials and harsh high-temperature heat treatment conditions.
The sodium silicate solution was mixed with the ammonium salt solution to form a sol, which was dialyzed and lyophilized to obtain an aerosol, which was then mixed with magnesium powder for heat treatment, and finally removed impurities by acid washing to prepare silicon/doped silicon porous nanosheets.
This method can efficiently and at low cost to prepare silicon/doped silicon porous nanosheets. The material has good electrochemical performance and excellent cycling stability, which significantly improves the rate performance and service life of the negative electrode material of lithium-ion battery.
Smart Images

Figure CN119660746A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a silicon / doped silicon porous nanosheet. Background Art
[0002] Silicon has the advantages of high theoretical specific capacity, abundant reserves and low discharge platform, and is considered to be an ideal choice for the negative electrode material of the new generation of high energy density lithium-ion batteries. However, silicon negative electrode materials also have some intrinsic problems that need to be solved, including huge volume changes (~300%) during lithium insertion and extraction and extremely low intrinsic conductivity (10 -3 S / cm) and the lithium ion diffusion coefficient (10 -14 ~10 -13 cm 2 / s), etc., which seriously hinders the commercial application of silicon negative electrode materials.
[0003] Nanoporous sheet structures can effectively buffer the volume expansion of silicon negative electrodes during lithium insertion and extraction. The sheet assembly formed by interconnected nanoparticles has good mechanical and structural stability, which is beneficial to inhibit structural deterioration and material pulverization during the charge and discharge process; and the abundant nanopores can provide sufficient space to accommodate the volume expansion of silicon nanoparticles, alleviating the mechanical stress caused by volume deformation of silicon materials during alloying / de-alloying. At the same time, porous nanosheet materials can also provide fast electron / ion mixed transmission channels. Among them, the porous sheet structure can shorten the lithium ion transmission path, accelerate electrolyte penetration and lithium ion diffusion, and the interconnected structure between silicon nanoparticles is conducive to rapid electron transmission. Therefore, two-dimensional porous silicon nanosheet negative electrode materials are expected to overcome the intrinsic problems of large volume deformation and poor charge transmission capacity during lithium insertion and extraction.
[0004] At present, two-dimensional porous silicon nanosheets are often synthesized using templates such as graphene oxide nanosheets and water-soluble salts. These template methods generally have problems such as high production cost, complicated synthesis process, and difficulty in regulating and optimizing the microstructure of silicon nanosheets and lithium storage performance. In addition, the addition of other elements to silicon materials to improve their conductivity generally requires high-temperature heat treatment, and the preparation conditions are harsh and complex, and it is difficult to achieve uniform doping of elements. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a method for preparing silicon / doped silicon porous nanosheets, which can efficiently and low-cost prepare silicon / doped silicon porous nanosheets, and the prepared silicon / doped silicon porous nanosheets have good electrochemical properties and excellent cycle stability when used as negative electrode materials for lithium-ion batteries.
[0006] Technical solution: The method for preparing silicon / doped silicon porous nanosheets of the present invention comprises the following steps:
[0007] (1) mixing a sodium silicate solution and an ammonium salt solution to obtain a sol after reaction;
[0008] (2) dialyzing the sol, and then freeze-drying the uniform and stable sol from which impurity ions have been removed to obtain an aerosol;
[0009] (3) mixing the aerosol with magnesium powder, performing magnesium heat treatment after mixing, and washing the product after magnesium heat treatment with acid and drying to obtain silicon / doped silicon porous nanosheets.
[0010] Wherein, in step (1), when preparing silicon porous nanosheets, the ammonium salt is at least one of ammonium sulfate, ammonium nitrate or ammonium chloride.
[0011] Wherein, in step (1), when preparing doped silicon porous nanosheets, the ammonium salt is ammonium dihydrogen phosphate and / or ammonium pentaborate.
[0012] Wherein, in step (1), the sodium silicate concentration in the sodium silicate solution is 0.05 to 1.00 mol / L; and the ammonium salt concentration in the ammonium salt solution is 0.05 to 1.00 mol / L.
[0013] Wherein, in step (1), the mixing volume ratio of the sodium silicate solution and the ammonium salt solution is 1:5 to 5:1.
[0014] Wherein, in step (1), the reaction time is 0.5 to 24 hours.
[0015] Wherein, in step (3), the mixing mass ratio of the aerosol to the magnesium powder is 1:2 to 2:1.
[0016] Wherein, in step (3), the temperature of the magnesium heat treatment is 600-800° C.; and the time of the magnesium heat treatment is 1-12 hours.
[0017] Wherein, in step (3), the silicon / doped silicon porous nanosheet is a porous sheet structure formed by assembling silicon nanoparticles or doped silicon nanoparticles in two-dimensional directions.
[0018] In the method of the present invention, silicate ions and ammonium ions undergo a rapid double hydrolysis reaction simultaneously, thereby obtaining a stable silica or doped silica sol; then the silica or doped silica sol is directly frozen, and the mechanism of dynamic growth of ice crystals to extrude sol particles and assemble into sheets is utilized to prepare silica or doped silica nanosheets; then, magnesium heat treatment is performed on the silica or doped silica nanosheets, and since the obtained silica or doped silica nanosheets have excellent mechanical and structural stability, the silica or doped silica nanosheets are reduced to silicon or doped silicon nanosheets during the magnesium heat treatment process, and the magnesium oxide generated by the reaction is removed by acid washing, leaving abundant holes in the silicon and doped silicon nanosheets, thereby finally forming a porous sheet structure of silicon / doped silicon.
[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the silicon or doped silicon porous nanosheets prepared by the method of the present invention can effectively buffer the volume expansion of the silicon negative electrode during the process of lithium insertion and extraction, the sheet assembly formed by interconnecting nanoparticles has good mechanical and structural stability, and the abundant nanopores can also provide sufficient space to accommodate the volume expansion of silicon nanoparticles; at the same time, the porous nanosheet material can provide a fast electron / ion mixed transmission channel, the porous sheet structure can shorten the lithium ion transmission path, accelerate the electrolyte penetration and lithium ion diffusion, and the interconnection structure between silicon nanoparticles is conducive to the rapid transmission of electrons; and the electronic conductivity of the silicon material can be further improved by in-situ doping, thereby significantly improving its rate performance. Therefore, when the silicon / doped silicon porous nanosheet prepared by the present invention is used as a negative electrode material for lithium ion batteries, it has excellent cycle stability, charge transfer capacity, long service life and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image (10 μm) of the silicon nanosheet prepared in Example 1;
[0021] Figure 2 This is a high-resolution transmission electron microscopy image (5 nm) of the silicon nanosheet prepared in Example 1;
[0022] Figure 3 This is a cycle performance diagram of the silicon nanosheet prepared in Example 1;
[0023] Figure 4 This is a rate performance diagram of the silicon nanosheets prepared in Example 1;
[0024] Figure 5 This is a scanning electron microscope image (10 μm) of the P-doped silicon nanosheet prepared in Example 2;
[0025] Figure 6 This is a high-resolution transmission electron microscopy image (5 nm) of the P-doped silicon nanosheets prepared in Example 2;
[0026] Figure 7 This is a cycle performance diagram of the P-doped silicon nanosheets prepared in Example 2;
[0027] Figure 8 This is a rate performance diagram of the P-doped silicon nanosheets prepared in Example 2. DETAILED DESCRIPTION
[0028] Example 1
[0029] The method for preparing the porous silicon nanosheet of the present invention comprises the following steps:
[0030] (1) dissolving sodium silicate in deionized water to obtain a sodium silicate solution, wherein the concentration of sodium silicate in the sodium silicate solution is 0.25 mol / L; dissolving ammonium sulfate in deionized water to obtain an ammonium sulfate solution, wherein the concentration of ammonium sulfate in the ammonium sulfate solution is 0.25 mol / L; then mixing the sodium silicate solution and the ammonium sulfate solution in a volume ratio of 1:1, and reacting for 2 hours to obtain a silica sol;
[0031] (2) dialyzing the silica sol until impurity ions are removed to obtain a uniform and stable silica sol; freeze-drying the silica sol to obtain a silica aerosol;
[0032] (3) Silica aerosol and magnesium powder are mixed in a mass ratio of 1:1, and after the mixture is evenly mixed, magnesium heat treatment is performed at 650°C in an argon atmosphere for 4 hours. The product after magnesium heat treatment is washed with acid and dried to obtain a two-dimensional silicon porous nanosheet.
[0033] Depend on Figure 1 It can be seen that the silicon nanosheets prepared in Example 1 present a typical two-dimensional sheet structure, which is composed of interconnected silicon nanoparticles and has abundant nanopores. Figure 2 ) It can be seen that the interplanar spacing in the silicon nanosheet is 0.31nm, corresponding to the 111 crystal plane of silicon. In order to verify the efficacy of the silicon nanosheet prepared in Example 1, the silicon nanosheet prepared in Example 1 was used as a negative electrode material for a lithium ion battery to carry out an electrochemical performance test. From the cycle performance diagram ( Figure 3 ) It can be seen that the silicon nanosheet negative electrode material is 0.5A·g -1 After 200 cycles at a current density of 1.3447 W, its discharge capacity is still as high as 1346.6 mAh g -1 , the capacity retention rate is 62.6%, showing good cycle life and high reversible specific capacity; from the rate performance diagram ( Figure 4 ) It can be seen that the silicon nanosheet exhibits good rate characteristics. -1 At a current density of 1.5 %, its average discharge capacity can still reach 872.6 mAh g -1 .
[0034] Example 2
[0035] The method for preparing the P-doped silicon porous nanosheet of the present invention comprises the following steps:
[0036] (1) dissolving sodium silicate in deionized water to obtain a sodium silicate solution, wherein the concentration of sodium silicate in the sodium silicate solution is 0.25 mol / L; dissolving ammonium dihydrogen phosphate in deionized water to obtain an ammonium dihydrogen phosphate solution, wherein the concentration of ammonium dihydrogen phosphate in the ammonium dihydrogen phosphate solution is 0.25 mol / L; then mixing the sodium silicate solution and the ammonium dihydrogen phosphate solution in a volume ratio of 1:1, reacting for 2 hours to obtain a P-doped silica sol;
[0037] (2) dialyzing the sol until the impurity ions are removed to obtain a uniform and stable P-doped silica sol; freeze-drying the P-doped silica sol to obtain a P-doped silica aerosol;
[0038] (3) P-doped silica aerosol and magnesium powder were mixed in a mass ratio of 1:1, and after being evenly mixed, magnesium heat treatment was performed at 650°C in an argon atmosphere for 4 hours. The product after magnesium heat treatment was washed with acid and dried to obtain a two-dimensional P-doped silicon porous nanosheet.
[0039] Depend on Figure 5 It can be seen that the P-doped silicon nanosheets prepared in Example 2 present a typical two-dimensional sheet structure, which is formed by interconnecting P-doped silicon nanoparticles and has abundant nanopores. Figure 6 It can be seen that the interplanar spacing of the P-doped silicon nanosheet is 0.31 nm, corresponding to the 111 crystal plane of silicon. In order to verify the efficacy of the P-doped silicon nanosheet prepared in Example 2, it was used as a negative electrode material for lithium-ion batteries to carry out electrochemical performance tests. From the cycle performance diagram ( Figure 7 ) It can be seen that the P-doped silicon nanosheet negative electrode material is at 0.5A·g -1 After 200 cycles at a current density of 1.34 W, its discharge capacity is still as high as 2176.2 mAh g -1 , no obvious capacity decay occurs, showing excellent cycle life and high reversible specific capacity; from the rate performance diagram ( Figure 8 ) It can be seen that P-doped silicon nanosheets have excellent rate characteristics. -1 At a current density of 1.547 W, its average discharge capacity can still reach 1590.3 mAh g -1 .
[0040] Example 3
[0041] The method for preparing B-doped silicon porous nanosheets of the present invention comprises the following steps:
[0042] (1) dissolving sodium silicate in deionized water to obtain a sodium silicate solution, wherein the concentration of sodium silicate in the sodium silicate solution is 0.05 mol / L; dissolving ammonium pentaborate in deionized water to obtain an ammonium pentaborate solution, wherein the concentration of ammonium pentaborate in the ammonium pentaborate solution is 1.00 mol / L; then mixing the sodium silicate solution and the ammonium pentaborate solution in a volume ratio of 5:1, reacting for 0.5 hours to obtain a B-doped silica sol;
[0043] (2) dialyzing the sol until the impurity ions are removed to obtain a uniform and stable B-doped silica sol; freeze-drying the B-doped silica sol to obtain a B-doped silica aerosol;
[0044] (3) The B-doped silica aerosol and magnesium powder were mixed in a mass ratio of 1:1.5. After the mixture was evenly mixed, a magnesium heat treatment was performed at 600°C in an argon atmosphere for 12 hours. The product after the magnesium heat treatment was washed with acid and dried to obtain a two-dimensional B-doped silicon porous nanosheet.
[0045] The B-doped silicon nanosheets prepared in Example 3 also present a typical two-dimensional porous sheet structure.
[0046] Example 4
[0047] The method for preparing the porous silicon nanosheet of the present invention comprises the following steps:
[0048] (1) dissolving sodium silicate in deionized water to obtain a sodium silicate solution, wherein the concentration of sodium silicate in the sodium silicate solution is 0.50 mol / L, and dissolving ammonium nitrate in deionized water to obtain an ammonium nitrate solution, wherein the concentration of ammonium nitrate in the ammonium nitrate solution is 0.05 mol / L; then mixing the sodium silicate solution and the ammonium nitrate solution in a volume ratio of 1:5, and reacting for 12 hours to obtain a silica sol;
[0049] (2) dialyzing the silica sol until impurity ions are removed to obtain a uniform and stable silica sol; freeze-drying the silica sol to obtain a silica aerosol;
[0050] (3) Silica aerosol and magnesium powder are mixed in a mass ratio of 1:2, and after the mixture is evenly mixed, magnesium heat treatment is performed in an argon atmosphere at 700°C for 6 hours. The product after magnesium heat treatment is washed with acid and dried to obtain a two-dimensional silicon porous nanosheet.
[0051] The silicon nanosheets prepared in Example 4 also present a typical two-dimensional porous sheet structure.
[0052] Example 5
[0053] The method for preparing the porous silicon nanosheet of the present invention comprises the following steps:
[0054] (1) dissolving sodium silicate in deionized water to obtain a sodium silicate solution, wherein the concentration of sodium silicate in the sodium silicate solution is 1.00 mol / L, and dissolving ammonium chloride in deionized water to obtain an ammonium chloride solution, wherein the concentration of ammonium chloride in the ammonium chloride solution is 0.05 mol / L; then mixing the sodium silicate solution and the ammonium chloride solution in a volume ratio of 1:5, and reacting for 24 hours to obtain a silica sol;
[0055] (2) dialyzing the silica sol until the impurity ions are removed to obtain a uniform and stable silica sol; freeze-drying the silica sol to obtain a silica aerosol;
[0056] (3) Silica aerosol and magnesium powder are mixed in a mass ratio of 2:1, and after being evenly mixed, magnesium heat treatment is performed in an argon atmosphere at 800°C for 1 hour. The product after magnesium heat treatment is washed with acid and dried to obtain a two-dimensional silicon porous nanosheet.
[0057] The silicon nanosheets prepared in Example 5 also present a typical two-dimensional porous sheet structure.
[0058] Table 1 shows the electrochemical properties of the silicon nanosheets prepared in Examples 1 to 2 and the silicon nanosheets prepared in the prior art.
[0059]
[0060] As shown in Table 1, the silicon / doped silicon porous nanosheet negative electrode material prepared by the present invention has excellent electrochemical performance. -1 At a current density of , it still has a high reversible specific capacity and capacity retention rate after 200 cycles, which are significantly higher than those of silicon nanosheets prepared by other methods.
Claims
1. A method for preparing silicon / doped silicon porous nanosheets, characterized in that: The steps include: (1) mixing a sodium silicate solution and an ammonium salt solution to obtain a sol after reaction; (2) dialyzing the sol, and then freeze-drying the sol from which impurity ions have been removed to obtain an aerosol; (3) mixing the aerosol with magnesium powder, performing magnesium heat treatment after mixing, and washing the product after magnesium heat treatment with acid and drying to obtain silicon / doped silicon porous nanosheets.
2. The preparation method according to claim 1, characterized in that: In step (1), when preparing silicon porous nanosheets, the ammonium salt is at least one of ammonium sulfate, ammonium nitrate or ammonium chloride.
3. The preparation method according to claim 1, characterized in that: In step (1), when preparing doped silicon porous nanosheets, the ammonium salt is ammonium dihydrogen phosphate and / or ammonium pentaborate.
4. The preparation method according to claim 1, characterized in that: In step (1), the sodium silicate solution has a sodium silicate concentration of 0.05 to 1.00 mol / L; and the ammonium salt solution has an ammonium salt concentration of 0.05 to 1.00 mol / L.
5. The preparation method according to claim 1, characterized in that: In step (1), the mixing volume ratio of the sodium silicate solution and the ammonium salt solution is 1:5 to 5:
1.
6. The preparation method according to claim 1, characterized in that: In step (1), the reaction time is 0.5 to 24 hours.
7. The preparation method according to claim 1, characterized in that: In step (3), the mixing mass ratio of the aerosol to the magnesium powder is 1:2 to 2:
1.
8. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the magnesium heat treatment is 600 to 800° C.; and the time of the magnesium heat treatment is 1 to 12 hours.
9. The preparation method according to claim 1, characterized in that: In step (3), the silicon / doped silicon porous nanosheet is a porous sheet structure formed by assembling silicon nanoparticles or doped silicon nanoparticles in two-dimensional directions.